A location–based context–aware service discovery approach for cycling experience. (20th August 2014) - Chen, Duen–Kai; Chang, Feng–Cheng; Lin, Szu–Yin
This study explored the use of context–aware information to facilitate web service discovery in a ubiquitous computing setting. Consumer electronics and internet access enable ubiquitous computing and have played an essential part in our daily lives, including cycling experience. Future applications for cyclists will be required to interact with multiple specialised services. In this study, a service–oriented architecture (SOA)–based service discovery framework that is implemented using the extensible messaging and presence protocol (XMPP) technology is proposed, and the framework design is presented. An example of a restaurant recommendation system for cyclists is highlighted as a proof of concept prototype to demonstrate and investigate the feasibility and effectiveness of the proposed framework.